Promoting active behaviours in schoolchildren using the socio-ecological model in the physical education class: study protocol of the ACTIBESE project - Fernando Rodríguez-Rodríguez; Carlos Cristi-Montero; Natalia Zurita-Corvalán; Caroline Brand; Jorge Mota; Palma Chillón; Anelise Reis Gaya; Javier Brazo-Sayavera; Nicolás Aguilar-Farias (BMC Pediatrics)
Abstract Background The correlation between parental and child physical activity levels has been the subject of significant investigation. Existing research has illuminated this association, particularly emphasising its influence during childhood. However, as children transition into adolescence, this relationship appears to weaken. Despite the recognised importance of parental involvement in promoting physical activity among children, scant attention has been directed towards understanding effective strategies and interventions to bolster this relationship. Consequently, there exists a critical gap in the literature concerning actionable measures to enhance parent-child physical activity engagement during the pivotal stage of adolescence. Methods The ACTIBESE project aims to assess and intervene in Chilean schoolchildren’s active behaviours by examining the influence of personal, interpersonal, and school factors. This study includes a cross-sectional and intervention study involving schools in the Valparaíso and Araucanía Regions, representing urban and rural areas. Participants, divided into children (8–11 years old) and adolescents (12–16 years old), will undergo a comprehensive evaluation, including sociodemographic characteristics, physical activity (PA) levels, parental and peer support, teaching styles of the teachers, and school environment characteristics. In the intervention study, a 5-month continuous training program for teachers will be implemented, focusing on improving teaching styles and enhancing teaching competencies related to physical education and health classes. The research will use mixed models, ANCOVA, and logistic regressions for data analysis, network analysis, exploratory factors analysis, and structural equation modelling. Discussion Through innovative research methods, interventions involving schoolteachers, and a diverse geographical scope, this project aims to make significant contributions to both the scientific understanding of promoting PA and public policy efforts aimed at improving the health and well-being of school-aged children. The ACTIBESE project’s multifaceted approach, considering school, family, and peer influences, is well positioned to contribute significantly to promoting AB and addressing the alarming decline in PA levels among Chilean youth.